Effect of Iron Content on Thermal Conductivity of Ferropericlase: Implications for Planetary Mantle Dynamics. Issue 7 (30th March 2023) - Zhang, Youyue; Yoshino, Takashi; Osako, Masahiro
Abstract: We have simultaneously measured thermal conductivity ( λ ) and thermal diffusivity ( κ ) for polycrystalline ferropericlase with different Fe contents (Fp3, Fp5, Fp10, Fp20, Fp30 and Fp50 ) up to 23 GPa and 1100 K by a pulse heating method. Experiment results reveals that even small amounts of Fe in ferropericlase can strongly reduce the thermal conductivity by several times at low temperature compared with MgO periclase. With increasing Fe in ferropericlase, both their pressure and temperature dependence decrease. λ of Fe‐bearing ferropericlase is not sensitive to temperature compared with silicates and shows a tendency of first increasing and then decreasing with increasing temperature. A universal equation was derived to estimate λ of ferropericlase with arbitrary composition under mantle conditions. The low λ values of Fe‐rich ferropericlase can explain one possible origin of ultralow velocity zones. This study suggests that Fe content in ferropericlase is an important factor controlling the cooling history of terrestrial planets. Plain Language Summary: To understand different roles of ferropericlase in heat transport during the evolution of terrestrial planet, pressure, temperature, and compositional dependence of thermal conductivity ( λ ) of ferropericlase need to be well constrained. We measured thermal conductivity and thermal diffusivity of ferropericlase with different Fe content simultaneously under high pressure and high temperature. The measurement results revealed a dramatic effect of Fe: a small addition of Fe causes a decrease in the absolute value and pressure dependence of ferropericlase by several times compared with end member MgO. Fe substitution also reduces the temperature sensitivity of thermal conductivity of ferropericlase, leading to nonmonotonic temperature dependence. Based on the systematic measurement data, we derive a universal equation as an applicable tool to estimate thermal conductivity of ferropericlase with variable compositions as functions of temperature and pressure. The results suggest that Fe‐poor ferropericlase ( X Fe  < 0.1) is a thermal conductor while Fe‐rich ferropericlase ( X Fe  ≥ 0.3) is likely to work as a thermal insulator under terrestrial planet mantle conditions. The highly composition‐dependent λ of ferropericlase suggests that the crystallization sequence of ferropericlase may influence the magma ocean cooling of terrestrial planets and result in thermal heterogeneity in the deep mantle. Key Points: We simultaneously measured the thermal conductivity and diffusivity of ferropericlase with different Fe contents by pulse heating method A dramatic effect of Fe on pressure and temperature dependence of thermal conductivity of ferropericlase was found The low λ of Fe‐rich ferropericlase at the bottom of the mantle supports patches of Fe‐rich materials as an origin for ultralow velocity zones